Advancements towards the implementation of clinical phase‐contrast breast computed tomography at Elettra. (17th June 2019) - Longo, Renata; Arfelli, Fulvia; Bonazza, Deborah; Bottigli, Ubaldo; Brombal, Luca; Contillo, Adriano; Cova, Maria A.; Delogu, Pasquale; Di Lillo, Francesca; Di Trapani, Vittorio; Donato, Sandro; Dreossi, Diego; et al.
Abstract : Major steps towards the clinical implementation of phase‐contrast breast computed tomography at Elettra, including software, hardware and protocol upgrades, are detailed. Imaging results and comparisons with conventional X‐ray mammography and histology indicate that synchrotron‐radiation‐based breast computed tomography is capable of providing unparalleled three‐dimensional insights of breast morphology at clinically acceptable doses. Abstract : Breast computed tomography (BCT) is an emerging application of X‐ray tomography in radiological practice. A few clinical prototypes are under evaluation in hospitals and new systems are under development aiming at improving spatial and contrast resolution and reducing delivered dose. At the same time, synchrotron‐radiation phase‐contrast mammography has been demonstrated to offer substantial advantages when compared with conventional mammography. At Elettra, the Italian synchrotron radiation facility, a clinical program of phase‐contrast BCT based on the free‐space propagation approach is under development. In this paper, full‐volume breast samples imaged with a beam energy of 32 keV delivering a mean glandular dose of 5 mGy are presented. The whole acquisition setup mimics a clinical study in order to evaluate its feasibility in terms of acquisition time and image quality. Acquisitions are performed using a high‐resolution CdTe photon‐counting detector and the projection data are processed via a phase‐retrieval algorithm. Tomographic reconstructions are compared with conventional mammographic images acquired prior to surgery and with histologic examinations. Results indicate that BCT with monochromatic beam and free‐space propagation phase‐contrast imaging provide relevant three‐dimensional insights of breast morphology at clinically acceptable doses and scan times.